2012
DOI: 10.1100/2012/312463
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome in Patients with Psoriasis

Abstract: Background. Psoriasis is a chronic inflammatory skin disorder in which proinflammatory cytokines including IL-6 and TNF-α increase both locally and systematically. It is thought that chronic inflammation results in metabolic diseases and proinflammatory cytokines give rise to the development of atherogenesis, peripheral insulin resistance, hypertension, and type 2 diabetes. Our aim was to investigate the prevalence of metabolic syndrome in patients with psoriasis vulgaris. Methods. Study consisted of 115 plaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
56
4
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 17 publications
7
56
4
7
Order By: Relevance
“…This observation is in agreement with many studies, which have shown a significantly higher prevalence of metabolic syndrome among psoriasis patients compared to controls. 6,10,14 However, this finding may not be comparable with the investigations done in different geographical milieu viz. Bangalore, Kashmir and Mumbai, as they did not use the Asian modification for waist circumference.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…This observation is in agreement with many studies, which have shown a significantly higher prevalence of metabolic syndrome among psoriasis patients compared to controls. 6,10,14 However, this finding may not be comparable with the investigations done in different geographical milieu viz. Bangalore, Kashmir and Mumbai, as they did not use the Asian modification for waist circumference.…”
Section: Discussioncontrasting
confidence: 51%
“…10,14 But this is in contrast to the study by Zindancı I et al from Turkey. 6 Regarding distribution pattern of psoriatic cases, in our study out total 50 cases, 39 had psoriasis vulgaris, 6 had psoriatic erythroderma and 4 patients had palmoplantar psoriasis and one patient had acute generalized pustular psoriasis. Of the 39 cases with psoriasis vulgaris, psoriasis was stable in 35 patients and unstable in 4 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with the study by Lakshmi et al and Zindancı et al but in contrast to study by Gisondi et al in which prevalence of MetS was independent of gender. 10,14,7 The possible explanation for higher prevalence of metabolic syndrome in females in our study could be that most of the women in our region are housewives having relatively sedentary lifestyle and limited outdoor activities.…”
Section: Discussionmentioning
confidence: 72%
“…Obezite ve psoriasis ilişkisi ile ilgili çok sayıda çalışma yapılmıştır. Bazı çalışmalarda obezite, psoriasis şiddeti ile ilişkili bulunurken bazılarında ilişkisiz olarak bulunmuştur [10][11][12][13][14][15][16][17] . Sunduğumuz çalışmada obezite ve psoriasis şiddeti zayıf ilişkili olarak tespit edilmiştir.…”
Section: Discussionunclassified